Selective Inhibition of the MK2 Pathway: Data From a Phase IIa Randomized Clinical Trial in Rheumatoid Arthritis. Issue 2 (5th January 2023) - Gordon, David; Kivitz, Alan; Singhal, Atul; Burt, David; Bangs, Madison C.; Huff, Emma E.; Hope, Heidi Rath; Monahan, Joseph B.
Abstract : Objective: The study objective was to evaluate the safety, tolerability, pharmacodynamics, and preliminary efficacy of ATI‐450 with methotrexate in patients with rheumatoid arthritis (RA). Methods: A parallel‐assignment, placebo‐controlled, investigator‐blinded/patient‐blinded multicenter study evaluated patients with moderate‐to‐severe RA aged 18 to 70 years. Eligible patients were randomized (1:1) to ATI‐450 50‐mg oral tablets twice daily or placebo with a stable weekly dose of methotrexate for 12 weeks. The primary objective was to assess ATI‐450 safety and tolerability. The secondary objectives were to assess the median percentage change from baseline high‐sensitivity C‐reactive protein (hs‐CRP) levels, the mean change from baseline in Disease Activity Score in 28 joints based on CRP level (DAS28‐CRP) and Rheumatoid Arthritis Magnetic Resonance Imaging Score hand‐wrist assessments of synovitis or bone erosion at week 12, and the proportion of patients with American College of Rheumatology 20/50/70 (ACR 20/50/70) and with DAS28‐CRP scores of less than 2.6. The exploratory outcomes were change from baseline in endogenous and ex vivo–stimulated cytokine levels. Results: ATI‐450 was well tolerated with no severe adverse events reported. ATI‐450 reduced median hs‐CRP levels by 42% or more at all posttreatment timepoints. In the ATI‐450 group, a mean (median) decrease in DAS28‐CRP score of 2.0 (2.1) was observed at week 12; proportions of patients with an ACR 20/50/70 response in the per‐protocol population were 60%, 33%, and 20%, respectively, at week 12. Endogenous plasma levels of key inflammatory cytokines (tumor necrosis factor α, macrophage inflammatory protein 1β, interleukin 6, interleukin 8) were reduced across the 12 treatment weeks. Conclusion: This is the first clinical study demonstrating that selective mitogen‐activated protein kinase (MAPK)–activated protein kinase 2 (MK2) pathway blockade leads to a sustained antiinflammatory effect. This suggests that targeting the MK2 pathway mitigates the tachyphylaxis observed with p38 MAPK inhibitors in RA and supports further exploration.